Does Nutritional Education Affect the Nutritional Status, Growth, and Development of Children with Pectus Excavatum? - Kahrıman, Meryem; Aritici Çolak, Gozde; Saǧlam, Duygu; Yüksel, Mustafa; Aslanhan, Sultan; Aslanhan, Sultan (Springer, 2025)
Purpose: Pectus deformity can cause cardiovascular, gastrointestinal, and genitourinary anomalies depending on the severity of the deformity, and this can affect the nutritional status of patients. This study aimed to investigate the effect of nutritional education on nutritional status and anthropometric measurements in patients with moderate pectus excavatum (PE). Methods: This study included patients diagnosed with pectus disease between the ages of 9 and 16 years. A questionnaire was administered, which included items regarding demographic information, eating habits, and physical activity levels. All patients were provided with nutritional education, including healthy diet principles. Subsequently, anthropometric measurements, such as height and body weight, were recorded, and 24-h food recall was taken. Results: A total of 40 children [31 (77.5%) men, 9 (22.5%) women] diagnosed with PE and moderate deformity severity participated in the study. After the provision of nutritional education, the patients’ body weight, WHO height and body mass index for age, as well as intake of energy, protein, and fat significantly increased. Conclusion: This study showed that nutritional education can improve the nutritional status of patients with moderate PE as it leads to an increase in anthropometric measurements and food/nutrient intake. Therefore, it would be beneficial to refer patients to a dietician to implement longer-term and improved educational models.
Keywords: Deformity; Education; Medical nutrition therapy; Pectus excavatum